Hashimoto’s thyroiditis and its activity status influence the assessment of lymph node metastasis of thyroid cancer - Yan, Caigu; Zhao, Yuxuan; Zhang, Qingyu; He, Xianghui (Frontiers in Endocrinology, 2025)
Background and purposeHashimoto’s thyroiditis plays a crucial role in the biological behavior of papillary thyroid carcinoma. The purpose of this study was to explore the impact of Hashimoto’s thyroiditis on the preoperative evaluation of thyroid cancer.MethodUnivariate and multivariate analyses were performed to explore the clinicopathological characteristics and the risk factors for lymph node metastasis (LNM) in 2,261 patients with papillary thyroid carcinoma.ResultsThe clinical data showed that the clinicopathological characteristics varied in different states of Hashimoto’s thyroiditis and levels of the thyroid peroxidase (TPO) antibody (p < 0.05). In cases without Hashimoto’s thyroiditis, the multivariate analysis showed that male sex (OR = 1.991, 95%CI = 1.574–2.517, p < 0.05) was the independent risk factor for LNM, but not in the cases with concurrent Hashimoto’s thyroiditis. The area under the receiver operating characteristic (ROC) curve of the non-Hashimoto’s thyroiditis cases was 0.727 (95% CI = 0.703–0.752, p < 0.05), while that in cases with Hashimoto’s thyroiditis was 0.632 (95% CI = 0.590–0.674, p < 0.05). Analysis of the differentially expressed genes in the different subgroups found that, in men, the differential genes among the different LNM statuses were mainly enriched in immune pathways, while in women and in younger patients, the genes were mainly enriched in cytokine and kinase pathways; in older patients, the genes were enriched in the extracellular matrix.ConclusionHashimoto’s thyroiditis can affect the preoperative evaluation of thyroid cancer. In addition, sex might affect the biological behavior of papillary thyroid carcinoma, which may result from the different immune and cellular statuses among different sexes and ages.